Etika Konselor Dalam Konseling Lintas Budaya - Asbi Asbi; Risty Dwi Apriananda; Okia Sari Sembiring (CV Edu Tech Jaya, 2024)
Counseling is assistance and guidance provided to individuals in general, and students in particular at madrasas or schools in order to improve the learning process. Counseling in madrasas or schools is carried out to meet the development of students in the process of emotional development and guidance in madrasas or schools and in the community. Ethics is closely related to the concept that an individual or group has to assess whether the actions they take are wrong or right, good or bad. Ethics is in the form of written regulations (codes) that are created systematically based on existing moral principles and, if necessary, can be used as a tool to measure all kinds of actions that are generally logically considered to deviate from ethical values. In the counseling process, errors or differences between clients' backgrounds often occur which makes the counseling process ineffective. Because different cultures create obstacles to communication, while communication is part of culture.